Bibliometric Analysis of Research Trends on Differentiated Learning In Merdeka Curriculum - Muhdi Harto; Misbah Misbah; Desy Purwasih; Fadilah Umar; Nurlaela Muhammad (Vidya Karya, 2023)
This research employed bibliometric analysis which aimed to analyze differentiated learning research trends in the Merdeka Curriculum and visualize them. The database used was Google Scholar. Based on the search results with the keyword "differentiated learning" through Publish or Perish (PoP), 41 articles were obtained and then analyzed into 28 articles based on predetermined criteria. Vosviewer was used to visualize the data obtained. From the results of the analysis, it was found that publications on differentiated learning start from 2020-2023, and the number continues to increase every year. The articles analyzed came from accredited national journals Sinta 3, Sinta 4, Sinta 5, and national journals. In addition, ten authors with the highest number of citations were obtained. The findings of this research show that differentiated learning topics in 2023 and beyond can continue to develop in various fields both in research subjects, subjects, implementation or the influence of differentiated learning on teacher competence.